Anteseden Ketepatwaktuan Publikasi Laporan Keuangan dengan Financial Distress sebagai Pemoderasi - Sastrawan, Ayu Ratih Kusumadewi; Badera, I Nyoman (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
The purpose of this study was to  determine the effect of going concern audit opinion and auditor switching on the timeliness of the publication of the financial statements, as well as financial distress as a moderating influence going concern audit opinion and auditor switching on the timeliness of the publication of the financial statements. This research was conducted in companies listed on the Indonesian Stock Exchange (BEI) of the year 2012-2016. Samples taken as many as 82 companies using purposive sampling technique. The data collection was conducted using non-participant observation. The analysis technique used is logistic regression and Moderated Regression Analysis (MRA). Analysis results showed that companies that get a going concern audit opinion or do auditor switching negatively affect the timeliness of the publication of the financial statements. Financial distress was not able to moderate the relationship between concern audit opinion with the timeliness of the publication of the financial statements, but able to moderate or reinforce negative effect relationship between the auditor switching to the timeliness of the publication of the financial statements.  Keywords: Timeliness Publication of Financial Statements, Going Concern Audit Opinion, Auditor Switching, Financial Distress